PENERAPAN STANDAR AKUNTANSI KEUANGAN ATAS AKTIVA LANCAR PADA LAPORAN KEUANGAN KOPERASI PRIMA KARYA SEJAHTERA - Ipahsari, Sri Wahyu; Maqsudi, Achmad (Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTThe financial statements of cooperatives are said to be in accordance with applicable standards, namely SAK ETAP if they include the preparation of Calculation of Operating Results, Statement of Changes in Equity, Balance Sheet, Cash Flow Report and Notes to Financial Statements. This study aims to determine how the application of accounting standards used by the Prima Karya Sejahtera Cooperative, whether it is in accordance with SAK ETAP. This study is a qualitative research with a descriptive analysis approach that aims to provide an overview of the state of objects based on facts that appear to use financial statement documentation. The results showed that the financial statements prepared by Koperasi Prima Karya Sejahtera up to now are in the form of Business Results Calculation Report, Changes in Equity and Balance Sheet. Koperasi Prima Karya Sejahtera has not yet presented the Cash Flow Report and Notes to Financial Statements to assess the financial performance of the cooperative, other than that the financial reports that have been presented by Koperasi Prima Karya Sejahtera are not Completely in accordance with the current accounting standards, namely SAK ETAP. Keywords: Financial Statements, Cooperatives and SAK ETAP